Speaking of Parties… Dueling Views in a Canonical Measure of Sophistication. Issue 1 (21st May 2019) - Kalmoe, Nathan P
Abstract: This article investigates fallout from a subtle but important conceptual disagreement over the nature of political parties that challenges a key measure of mass political sophistication. The American Voter 's typology assumes that sophisticated citizens notice the ideological abstractions defining parties. Alternatively, The Party Decides defines parties as group-based coalitions. The distinction is crucial for the "levels of conceptualization" measure, which considers ideological party views superior to group-oriented ones. Few people make ideological remarks about parties; many more describe links between parties and groups. Converse and colleagues take the scarcity of "ideologues" as evidence against mass sophistication, but a measure that might classify Party Decides –type comments in a lower tier may be invalid. How many citizens are misclassified? I parse decades of survey data to test whether sophistication in some group-centric citizens has gone unrecognized. It hasn't. Despite the conceptual threat, several tests show no evidence of hidden sophistication among these respondents overall or in subgroups, affirming the measure's rank-order. Group-centric citizens are right about parties, but even their brightest are no "ideologues."